(untitled) (Journal of the Bangladesh Agricultural University, 2024)
Gastrointestinal nematode infections of livestock are ranked in the top twenty diseases affecting small-holder farmers’ livestock. Mecistocirrus digitatus is one of the most prevalent parasitic nematode among the trichostrongylids causing severe health hazards leading to production losses in cattle worldwide. This study was conducted to explore the existence and genetic diversity of M. digitatus parasite populations from cattle characterizing second internal transcribed spacer (ITS-2) gene of nuclear ribosomal DNA (rDNA). A total of 23 adult Mecistocirrus parasites were collected from abomasa of slaughtered cattle from Mymensingh district of Bangladesh. After the extraction of DNA from adult parasites, ITS-2 of nuclear rDNA gene was amplified and sequenced. The edited and aligned sequences were employed for analysis to determine sequence variation and genetic diversity. All the sequences were found to have high identical ratio with M. digitatus of a published sequence and sequence identities ranged from 97.9% to 100%. Genetic analysis revealed 3 distinct ITS-2 genotypes among the M. digitatus isolates. The nucleotide and genotype diversities were 0.00089 and 0.170, respectively for ITS-2 sequences. Phylogenetic analysis (neighbour joining, maximum likelihood and maximum parsimony) of ITS-2 sequences indicated the existence of a single cluster within M. digitatus population in the study area. In conclusion, our study could confirm M. digitatus in the analyzed parasite isolates by amplifying and sequencing ITS-2 gene. Most of the isolates from our present study presented identical genotypes indicating that low genetically diversified parasites are circulating in Mymensingh region of Bangladesh. The findings of our study creates a basis for further molecular epidemiological surveys applying more M. digitatus parasite isolates from different regions of Bangladesh. J Bangladesh Agril Univ 19(1): 67–72, 2021 https://doi.org/10.5455/JBAU.6175